Pengembangan E-Modul untuk Melatih Kemampuan Literasi Membaca Peserta Didik SMA - Siti Tahany Rifa Faidah; Siti Sriyati; Didik Priyandoko (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop an E-Module to train high school students' reading literacy skills. The e-module was designed using Canva-assisted power point and saved in power point show. The power point show is then sent via WhatsApp for students to use. This research uses the development method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) according to. The implementation phase uses a pretest – posttest non-equivalent control group design to obtain information about the effect the developed E-Module. This research was conducted at a public high school in Cimahi City, West Java Province in February-March 2023. The sample for this study was taken by convenience sampling , namely 30 students from class XI IPA 1 as the experimental class and 30 students from class XI IPA 2 as the experimental class. control. The instruments and data collection techniques used in this study were the due diligence validation sheets, readability tests and reading literacy skills tests. The results showed that the feasibility test for the developed E-module showed very feasible criteria, the readability test showed a result of 80% with easy-to-understand criteria and the development of this E-module could increase reading literacy skills by 0.7 with high criteria on the indicator of finding information, 0.8 with high criteria on indicators of interpretation and integration and a score of 1 with high criteria on evaluating and reflecting indicators.